Email
logo

Ask Questions, Get Answers

X
 
Questions  >>  CBSE XI  >>  Math  >>  Sequences and Series
Answer
Comment
Share
Q)

Show that the sum of $(m+n)^{th}$ and $(m-n)^{th}$ terms of an A.P is twice its $m^{th}$ term.

1 Answer

Comment
A)
In an A.P. $n^{th}$ term = $t_n=a+(n-1)d$
$\Rightarrow\:t_{m+n}=a+(m+n-1)d$ ....(i) and
$t_{m-n}=a+(m-n-1)d.......$ (ii)
Adding (i) and (ii) we get
$t_{m+n}+t_{m-n}=(a+(m+n+1)d)+(a+(m-n-1)d)$
$\qquad\:\qquad=2a+(m+n-1+m-n-1)s$
$\qquad\qquad\:=2a+(2m-2)d=2(a+(m-1)d)=t_m$
Hence proved.
Help Clay6 to be free
Clay6 needs your help to survive. We have roughly 7 lakh students visiting us monthly. We want to keep our services free and improve with prompt help and advanced solutions by adding more teachers and infrastructure.

A small donation from you will help us reach that goal faster. Talk to your parents, teachers and school and spread the word about clay6. You can pay online or send a cheque.

Thanks for your support.
Continue
Please choose your payment mode to continue
Home Ask Homework Questions
Your payment for is successful.
Continue
...